2022
DOI: 10.1017/s0029665122001008
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition policy: developing scientific recommendations for food-based dietary guidelines for older adults living independently in Ireland

Abstract: Older adults (≥65 years) are the fastest growing population group. Thus, ensuring nutritional well-being of the ‘over-65s’ to optimise health is critically important. Older adults represent a diverse population – some are fit and healthy, others are frail and many live with chronic conditions. Up to 78% of older Irish adults living independently are overweight or obese. The present paper describes how these issues were accommodated into the development of food-based dietary guidelines for older adults living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Furthermore, participants with MetS consumed significantly more low-quality protein foods which were found to be carbohydrate-rich, lowfiber foods [56]. Within this context, it is worth noting that dietary guidelines for older adults in Ireland recommend a protein-dense diet, including high-quality protein foods, to maintain muscle mass and prevent sarcopenia [56,57] which is associated with increased risk of mortality [58][59][60]. Increasing the quantity and quality of protein may also help to maintain bone health and protect against frailty and falls [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participants with MetS consumed significantly more low-quality protein foods which were found to be carbohydrate-rich, lowfiber foods [56]. Within this context, it is worth noting that dietary guidelines for older adults in Ireland recommend a protein-dense diet, including high-quality protein foods, to maintain muscle mass and prevent sarcopenia [56,57] which is associated with increased risk of mortality [58][59][60]. Increasing the quantity and quality of protein may also help to maintain bone health and protect against frailty and falls [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…The current findings will have greatest relevance for aging adults who are at increased risk of vitamin B12 deficiency, despite typically having dietary B12 intakes, which exceed the current recommendation of 4 μg/d, as set by the European Food Safety Authority. ( 22 , 51 ) Using a comprehensive suite of B12 biomarkers, we recently reported a high prevalence of B12 deficiency in older Irish adults, particularly among those identified with atrophic gastritis or taking PPI medications, among whom 38% and 21%, respectively, were B12 deficient. ( 14 ) Notably, the intakes of crystalline vitamin B12 (10 μg/d), shown in the present study to be effective in optimizing B12 status and reducing the rate of BMD decline, are achievable through intervention with B12‐fortified foods.…”
Section: Discussionmentioning
confidence: 99%
“…Given the known beneficial effects of vitamin D supplementation on bone health, both treatment groups received vitamin D, therefore ensuring that any observed benefits of intervention on BMD could be attributed to B-vitamin intervention. The B-vitamin doses selected for this trial, although within the dietary ranges, were somewhat higher (with the exception of folate) than both recommended and habitual intakes of these B-vitamins in Irish and Northern Irish adults, (22) but nonetheless within the range achievable via a combination of natural and fortified food sources. All aspects of randomization were carried out by the Human Interventions Studies Unit (HISU) Clinical Trials Manager at UU.…”
Section: Study Design and Compliancementioning
confidence: 95%
“…Whether adherence to these dietary guidelines optimizes intrinsic capacity is less clear. Furthermore, given that older adults have different dietary requirements than the younger population, it has been suggested that a more specific dietary guideline is required for older adults [5].…”
Section: Introductionmentioning
confidence: 99%